Assessment of the perceived security among public transport users in Europe - Kalakou, S.; Adorean, C.; Lynce, A. R.; Medina Arguello, J. C.; Costa, M.; Pirra, M. (Gender and equality in transport. Proceedings of the 2021 Travel Demand Management Symposium, 2021)
Passenger experiences with public transport are expected to be safe, secure, comfortable, convenient and pleasant. However, this experience is often disrupted by harassment incidents, such as sexual, theft and verbal harassment that may affect passengers' perspective towards public transport services. Security perceptions and harassment experiences may vary according to gender and age. This study analyses the perceptions of 2413 citizens in six European cities over security aspects of public transport and potential measures that can improve these perceptions. Harassment experiences are also illustrated, and their patterns are discussed. The paper concludes with some recommendations to operators of public transport over enhancing the feeling of security and ameliorating negative experiences related to harassment.